2012
DOI: 10.1158/1078-0432.ccr-12-0605
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Profiling and Microsatellite Instability in Stage II and III Colon Cancer: An Assessment of Their Prognostic and Oxaliplatin Predictive Value

Abstract: Purpose The purpose of this study was to examine the prognostic and oxaliplatin predictive value of mismatch repair (MMR) status and common hot spot mutations, which we previously identified in stage II and III colon cancer. Experimental Design Mutations in BRAF, KRAS, NRAS, MET, and PIK3CA were profiled in 2,299 stage II and III colon tumors from National Surgical Adjuvant Breast and Bowel Project (NSABP) clinical trials C-07 (n = 1,836) and C-08 (n = 463) with Type Plex chemistry and mass spectrometry. C-0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
227
4
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 277 publications
(252 citation statements)
references
References 44 publications
18
227
4
3
Order By: Relevance
“…However, this eff ect may principally be manifest in metastatic disease. Th e lack of BRAF predictive eff ect in our data is consistent with recent fi ndings from Gavin et al ( 40 ) who showed that in stage II / III CRC, BRAF mutation is principally an indicator of poor prognosis aft er relapse and is hence associated with overall, but not DFS, survival.…”
Section: Discussionsupporting
confidence: 92%
“…However, this eff ect may principally be manifest in metastatic disease. Th e lack of BRAF predictive eff ect in our data is consistent with recent fi ndings from Gavin et al ( 40 ) who showed that in stage II / III CRC, BRAF mutation is principally an indicator of poor prognosis aft er relapse and is hence associated with overall, but not DFS, survival.…”
Section: Discussionsupporting
confidence: 92%
“…However, only limited data from prospective RCTs is available (Des Guetz et al, 2010;Kim et al, 2010). Gavin et al, in an analysis of 2299 stage II and stage III CRC patients from National Surgical Adjuvant Breast and Bowel Project (NSABP) C-07 [5-FU plus leucovorin (LV) ± oxaliplatin] and C-08 (FOLFOX ± bevacizumab) adjuvant studies showed that dMMR was prognostic for recurrence in CRC patients treated with FOLFOX (time to relapse [TTR] HR = 0.58; 95 % CI: 0.35-0.96; P = 0.03) compared to MSS CRC, however, the MMR status was not predictive of oxaliplatin efficacy (Gavin et al, 2012). Andre et al and colleagues in an analysis of the Multicenter International Study of Oxaliplatin/5-Fluorouracil/Leucovorin in the Adjuvant Treatment of Colon Cancer (MOSAIC) study evaluated MMR status in 986 of the 2240 enrolled patients.…”
Section: Msi As a Prognostic Marker With Adjuvant 5-fu Plus Oxaliplatmentioning
confidence: 99%
“…77 BRAF V600E mutation status and MMR proficiency were both prognostic factors associated with shorter overall survival times. 77,81 Other studies using multi-gene expression tests have not been able to show predictive value.…”
Section: Issues In Specific Tumor Typesmentioning
confidence: 92%
“…77 BRAF V600E mutation status and MMR proficiency were both prognostic factors associated with shorter overall survival times. 77,81 Other studies using multi-gene expression tests have not been able to show predictive value. Thus, identifying the molecular characteristics of colon tumors most likely to benefit from chemotherapy and the development of targeted agents remain high priorities for clinical trial design.…”
Section: Issues In Specific Tumor Typesmentioning
confidence: 92%
See 1 more Smart Citation